Management of product characteristics uncertainty based on formal logic and characteristics properties model - Dantan, J.Y.; Qureshi, A.J.; Antoine, J.F.; Eisenbart, B.; Blessing, L. (CIRP annals, 2013)
Uncertainty in product characteristics is ubiquitous in any engineering system at all the stages of product life-cycle. Considering uncertainty from different sources during the product design phase is critical to its reliable performance. This paper presents a framework integrating the uncertainty propagation through different product characteristics and its effect on product properties. The framework consists of three main parts: a descriptive model based on formal logic and characteristics properties model; a mathematical implementation through set theory and probabilistic approach; and an algorithm for design space evaluation and tolerancing. The application of framework is demonstrated through an industrial case study.